2015
DOI: 10.1021/acsnano.5b04843
|View full text |Cite
|
Sign up to set email alerts
|

Water Protects Graphitic Surface from Airborne Hydrocarbon Contamination

Abstract: The intrinsic wettability of graphitic materials, such as graphene and graphite, can be readily obscured by airborne hydrocarbon within 5-20 min of ambient air exposure. We report a convenient method to effectively preserve a freshly prepared graphitic surface simply through a water treatment technique. This approach significantly inhibits the hydrocarbon adsorption rate by a factor of ca. 20×, thus maintaining the intrinsic wetting behavior for many hours upon air exposure. Follow-up characterization shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
155
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(169 citation statements)
references
References 72 publications
14
155
0
Order By: Relevance
“…These findings are consistent with other surface sensitive measurements on basal plane HOPG, for example, the effect of ambient exposure on its contact angle at neutrality, 23 and our own recent work, which has…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with other surface sensitive measurements on basal plane HOPG, for example, the effect of ambient exposure on its contact angle at neutrality, 23 and our own recent work, which has…”
Section: Resultssupporting
confidence: 93%
“…[21][22][23] The presence of the latter is also reported to affect the intrinsic electrochemical response of graphite surfaces, either through the effect on the kinetics of heterogeneous electron transfer, [23][24][25][26] or on the capacitance of graphite/electrolyte interfaces. 27 Here we describe the effect of surface treatment, including ambient ageing, on the graphite electrowetting response and also attempt to generalise the phenomenon to other carbonaceous surfaces including graphene, with the aim of better understanding the specific electrode-electrolyte surface interactions responsible for the reversible wetting process.…”
Section: Introductionmentioning
confidence: 99%
“…[49][50][51][52][53][54][55] Moreover, they showed that electron transfer rates significantly deteriorate when the graphitic surface is exposed to air; 50 this has been corroborated through work by Velický and Dryfe et al, [56][57][58] Nioradze and Amemiya et al, [59][60][61] and Li and Liu et al 62 These results have salient implications for graphene and graphite electrodes and batteries. Taking into account a thin hydrocarbon layer, or controlling to restrict hydrocarbon adsorption, can substantially improve device performance.…”
Section: Implications Of Surface Contaminationmentioning
confidence: 88%
“…It is important to note that all experiments conducted by myself and my co-workers were taken on samples that were purchased new and once the sample got substantially thin it was replaced and no longer used for experiments. 62,70,[75][76][77] ZYA is the highest quality of HOPG and exfoliates nearly perfectly. Visually, there were no flakes or exfoliation-induced defects noticeable and all experimental testing was performed only on the visually pristine basal surface.…”
Section: Defects Caused By Exfoliationmentioning
confidence: 97%
“…Typical cleaning procedures result in clean graphene patches of only nanometer dimensions [25][26][27][28]. Polymethyl methacrylate (PMMA) is often used as an intermediate supporting polymer during 2D materials transfer; however, PMMA residues in particular have proven to be challenging to remove by typical cleaning procedures such as thermal annealing in Ar/H 2 [23], and until now prevention strategies have proven to be the most effective cure [29].…”
Section: In Situ Cleaning Of Graphenementioning
confidence: 99%